Analisis Kecerdasan Visual-Spasial dalam Menyelesaikan Masalah Dimensi Tiga Ditinjau dari Tingkatan Berpikir Van Hiele - Reza Adha; Sudi Prayitno; Syahrul Azmi (Pendidikan Matematika FKIP Universitas Mataram, 2026)
This study aims to describe students' visual–spatial intelligence in solving three-dimensional geometry problems based on van Hiele’s levels of geometric thinking. This research employed a qualitative approach with a descriptive research design. The subjects of this study were Grade XII science students of SMA Negeri 2 Labuapi. Data were collected through a van Hiele geometric thinking level test, a visual–spatial intelligence test, and interviews. The van Hiele test was administered to 21 students to classify their geometric thinking levels. The results showed that 16 students were at level 0, 3 students at level 1, and 2 students at level 2. Two students from each level were then selected as interview subjects. The findings indicate that students at level 0 did not fulfill the characteristics of visual–spatial intelligence. Students at level 1 fulfilled spatial perception, visualization, and spatial relation, while students at level 2 fulfilled spatial perception, visualization, spatial relation, and mental rotation. These results indicate that higher van Hiele thinking levels are associated with better visual–spatial intelligence in solving three-dimensional geometry problems.